Ultra-low energy LIF neuron using Si NIPIN diode for spiking neural networks - Das, B.; Schulze, J.; Ganguly, Udayan (IEEE Electron Device Letters, 2018)
An energy efficient neuron is essential for spiking neural network (SNN) to operate at low energy to mimic the human brain functionalities in hardware. Several CMOS-based Si transistors, memory devices, spintronic devices have been used as a neuron for SNN. However, the main concern is the energy efficiency for these neurons. In this letter, we experimentally demonstrate a Si-based CMOS compatible asymmetric NIPIN diode as a LIF neuron. First, we demonstrate the LIF neuron characteristics by comparing the spike-frequency (f) versus voltage curve with that of a simple LIF neuron model. This neuron shows a classical ReLU behavior, which is attractive for typical software neuron models. Then, we show an ultra-low energy consumption of ∼2 × 10-17J per spike at 10-nm node of this neuron, as NIPIN diode is highly scalable (4F2) due to its capacitorless structure. This is the lowest reported energy/spike for any LIF neuron for SNN application. Thus, the NIPIN is suitable for ultra-low energy LIF neuron application for energy efficient SNN.
CRIS-Team Scopus Importer:2021-06-29
Keywords: impact ionization; LIF neuron; Si NIPIN diode; spiking neural network